Intermolecular interactions and structural organization of a native chitin-chitosan hydrocolloid network resolved by solid-state NMR and molecular dynamics - Qinghui Cheng; Chunyan Lu; Xiufang Gong; Qingyan Wang; Siming Liao; Lihua Chen (Food Hydrocolloids, 2026)

Berberine inhibits ISG15 and pyroptosis to attenuate diabetic kidney disease inflammation and fibrosis - Lingzhi Huang; Qinqin Chen; Xiaoxiao Liu; Liuqing Wang; Xingyue Liao; Siming Yuan; Liqin Tang (Apoptosis, 2026)

Ultrasonic-enzymatic synergistic extraction of Ophiopogon japonicus polysaccharides: Structural characterization, in vitro hypoglycemic activity, and regulatory mechanism on human gut microbiota - Junlin Wu; Meng Wang; Yutong Liao; Sijie Huang; Xincheng Ye; Fengchuan Ma; Siming Zhu; Yunping Peng; Dan Xu (Food Bioscience, 2026)

Structural insights into polysaccharides in Ganoderma lucidum cell walls by solid-state NMR - Lihua Chen; Siming Liao; Qinghui Cheng (Carbohydrate Polymers, 2025)

Enhanced chitinase production by Bacillus paralicheniformis GXMU-J23.1: Optimization, genomic insights, and chitin degradation mechanism - Junjie Xie; Ligang Zhang; Kexin Yang; Hongyan Zhang; Mingguo Jiang; Siming Liao; Dengfeng Yang; Naikun Shen (Bioresource Technology, 2025)

Anticancer effect of hUC-MSC-derived exosome-mediated delivery of PMO-miR-146b-5p in colorectal cancer - Siming Yu; Ran Liao; Lu Bai; Madi Guo; Yu Zhang; Yumin Zhang; Qi Yang; Yushuai Song; Zhiwei Li; Qingwei Meng; Shubin Wang; Xiaoyi Huang (Drug Delivery and Translational Research, 2024)
Antisense oligonucleotide (ASO) is a novel therapeutic platform for targeted cancer therapy. Previously, we have demonstrated that miR-146b-5p plays an important role in colorectal cancer progression. However, a safe and effective strategy for delivery of an ASO to its targeted RNA remains as a major hurdle in translational advances. Human umbilical cord mesenchymal cell (hUC-MSC)–derived exosomes were used as vehicles to deliver an anti-miR-146b-5p ASO (PMO-146b). PMO-146b was assembled onto the surface of exosomes (e) through covalent conjugation to an anchor peptide CP05 (P) that recognized an exosomal surface marker, CD63, forming a complex named ePPMO-146b. After ePPMO-146b treatment, cell proliferation, uptake ability, and migration assays were performed, and epithelial-mesenchymal transition progression was evaluated in vitro. A mouse xenograft model was used to determine the antitumor effect and distribution of ePPMO-146b in vivo. ePPMO-146b was taken up by SW620 cells and effectively inhibited cell proliferation and migration . The conjugate also exerted antitumor efficacy in a xenograft mouse model of colon cancer by systematic administration, where PPMO-146b was enriched in tumor tissue. Our study highlights the potential of hUC-MSC-derived exosomes anchored with PPMO-146b as a novel safe and effective approach for PMO backboned ASO delivery. Graphical Abstract Schematic illustration of the preparation of an exosomal anchor peptide (CP05)-PMO that conjugately binds to exosomes from hUC-MSCs (ePPMO-146b) and the antitumor effect of ePPMO-146b in CRC, which occurs through the inhibition of Smad signaling and epithelial–mesenchymal transition.

Degradation characteristics of intracellular and extracellular ARGs during aerobic composting of swine manure under enrofloxacin stress - Jiaojiao Xu; Jielan Huang; Longhai Chen; Majian Chen; Xin Wen; Pengfei Zhang; Siming Li; Baohua Ma; Yongde Zou; Yan Wang; Xindi Liao; Yinbao Wu (Chemical Engineering Journal, 2023)

Characterization of a bifunctional alginate lyase as a new member of the polysaccharide lyase family 17 from a marine strain BP-2 - Guiyuan Huang; Shunhua Wen; Siming Liao; Qiaozhen Wang; Shihan Pan; Rongcan Zhang; Fu Lei; Wei Liao; Jie Feng; Shushi Huang (Biotechnology Letters, 2019)